3-[1-(4-Isobutylphenyl)ethyl]-4-[(E)-4-methylbenzylideneamino]-1H-1,2,4-triazole-5(4H)-thione - Fun, Hoong-Kun (International Union of Crystallography, 2008)
In the title compound, C(22)H(26)N(4)S, the dihedral angles formed by the triazole ring with the two benzene rings are 87.51 (3) and 20.98 (3)°. The benzene rings are inclined at 71.88 (2)°. An intramolecular C—H⋯S hydrogen bond generates an S(6) ring motif. The crystal packing is strengthened by intermolecular N—H⋯S hydrogen bonding and π–π stacking interactions between the triazole and benzene rings, with a centroid–centroid distance of 3.6618 (5) Å, together with N⋯N [2.1299 (9)–2.2121 (9) Å] short contacts and C—H⋯π interactions. In the crystal packing, molecules are stacked along the a axis.